2009
DOI: 10.1093/jac/dkp232
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-adherence to long-term highly active antiretroviral therapy: a 10 year follow-up analysis with correction for the bias induced by missing data

Abstract: Reasons for non-adherence depended on both psychosocial conditions and treatment-related characteristics. To improve long-term patient outcomes for those at risk of adherence failure, tailor-made patient-specific psychosocial interventions and regimen-based strategies with improved tolerance need to be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
64
3
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 41 publications
10
64
3
2
Order By: Relevance
“…Another recent study by Arroyo et al found no difference in adherence rates in patients receiving once or twice daily regimens [24]. A French study showed that nonadherence was independently associated with side effects, and having a three times or more daily dosing regimen in comparison to once or twice daily therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study by Arroyo et al found no difference in adherence rates in patients receiving once or twice daily regimens [24]. A French study showed that nonadherence was independently associated with side effects, and having a three times or more daily dosing regimen in comparison to once or twice daily therapy [25].…”
Section: Discussionmentioning
confidence: 99%
“…13 The role of side effects on treatment adherence has been discussed previously for drug-susceptible TB and other diseases that require long-term treatment, such as human immunodefi ciency virus/acquired immunedefi ciency syndrome. [14][15][16][17][18][19][20] The treatment of DR-TB is known to cause frequent severe side effects. [21][22][23] In the project in Yerevan, free, good quality monitoring and management of side effects was provided thanks to MSF support.…”
Section: Discussionmentioning
confidence: 99%
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified